Doctors' emotional reactions to recent death of a patient: cross sectional study of hospital doctors. Issue 7408 (24th July 2003) - Redinbaugh, Ellen M; Sullivan, Amy M; Block, Susan D; Gadmer, Nina M; Lakoma, Matthew; Mitchell, Ann M; Seltzer, Deborah; Wolford, Jennifer; Arnold, Robert M
Abstract: Objectives : To describe doctors' emotional reactions to the recent death of an "average" patient and to explore the effects of level of training on doctors' reactions. Design : Cross sectional study using quantitative and qualitative data. Setting : Two academic teaching hospitals in the United States. Participants : 188 doctors (attending physicians (equivalent to UK consultants), residents (equivalent to UK senior house officers), and interns (equivalent to UK junior house officers)) who cared for 68 patients who died in the hospital. Main outcome measures : Doctors' experiences in providing care, their emotional reactions to the patient's death, and their use of coping and social resources to manage their emotions. Results : Most doctors (139/188, 74%) reported satisfying experiences in caring for a dying patient. Doctors reported moderate levels of emotional impact (mean 4.7 (SD 2.4) on a 0-10 scale) from the death. Women and those doctors who had cared for the patient for a longer time experienced stronger emotional reactions. Level of training was not related to emotional reactions, but interns reported needing significantly more emotional support than attending physicians. Although most junior doctors discussed the patient's death with an attending physician, less than a quarter of interns and residents found senior teaching staff (attending physicians) to be the most helpful source of support. Conclusions : Doctors who spend a longer time caring for their patients get to know them better but this also makes them more vulnerable to feelings of loss when these patients die. Medical teams may benefit from debriefing within the department to give junior doctors an opportunity to share emotional responses and reflect on the patient's death.